Tinjauan Yuridis terhadap Kasus Kepemilikan Senjata Api dan Amunisi Ilegal di Indonesia - Angelica Angelica; Ahmad Irzal Fardiansyah; Fristia Berdian Tamza (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
This study aims to analyze the legal review of illegal firearms and ammunition ownership in Indonesia. The research method used in this study is the normative legal research method. The main data source in this study is secondary legal sources, consisting of Emergency Law No. 12 of 1951 and Law No. 8 of 1948 concerning the registration and granting of firearms ownership permits. The results of the study concluded that law enforcement against illegal firearms and ammunition ownership in Indonesia has been carried out in accordance with existing laws and regulations related to illegal firearms ownership, conducting investigations and law enforcement according to the facts in court and factors inhibiting law enforcement against illegal firearms and ammunition ownership in Indonesia in the form of legal factors, law enforcement, society, facilities and infrastructure, culture. The suggestion in this study is that there should be no difference in decision making and witnesses in law enforcement because of considering status, position, and economy so that law enforcement can be more optimal, and so that there are no obstacles to law enforcement, law enforcement officers need to increase supervision of the circulation of illegal firearms and ammunition through cooperation with community leaders, traditional leaders, law enforcement officers, and the media.